1995
DOI: 10.1002/hep.1840210518
|View full text |Cite
|
Sign up to set email alerts
|

Which is the best surgery for budd-chiari syndrome: Venous decompression or liver transplantation? a single-center experience with 50 patients

Abstract: The optimal treatment of Budd-Chiari syndrome (BCS) remains an open question. It is still a matter of controversial discussion whether venous decompression or liver transplantation is superior. To elucidate the role and prognosis of both surgical options in our own experience, a consecutive series of 50 patients treated between 1981 and 1993 was retrospectively analyzed. Twelve patients had different types of portosystemic shunts or local decompressive procedures, and transplantation was performed in 43 cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(64 citation statements)
references
References 21 publications
3
61
0
Order By: Relevance
“…Other studies, mostly case series from surgical units, report on high survival rates after PSS with 5-year survival of 57% 11 to 94%. 9,10 However, most of these studies do not provide data on patient selection criteria, which play a major role in the long-term results of treatment, 21 nor do they take account of differences in time-point of shunting within the clinical course of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, mostly case series from surgical units, report on high survival rates after PSS with 5-year survival of 57% 11 to 94%. 9,10 However, most of these studies do not provide data on patient selection criteria, which play a major role in the long-term results of treatment, 21 nor do they take account of differences in time-point of shunting within the clinical course of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Institutional experience and preferences as well as patient selection play a major role in the choice of treatment. 21 This creates a large degree of heterogeneity between study populations. Most studies on the effect of therapeutic interventions, in particular PSS, do not report selection criteria nor do they control for differences in baseline characteristics between patients who do or do not undergo PSS.…”
Section: Bcsmentioning
confidence: 99%
“…Other surgical techniques reported in that and other series had roughly unacceptable outcomes when reported [30,31,33] . We recently described a patient with IVC obstruction near the atrium and a previous severe complication of a trial of endovascular management, who had an excellent outcome after the replacement of the obstructed segment of the IVC with a caval homograft [35] .…”
Section: Treatments For Budd-chiari Syndromementioning
confidence: 67%
“…In the same series, the mortality rates of patients with IVC involvement were very high after traditional surgery (mesoatrial shunts) and better results were reported using another technique (SSPCS + cavoatrial shunt) in 18 patients, all surviving after a follow-up of 5 to 25 years [32] . However, outcome after surgical shunt is variable and worse results were reported by others [30,31,33] . In most of the above series, patients with liver failure were not considered for surgery but for liver transplantation [31][32][33] .…”
Section: Treatments For Budd-chiari Syndromementioning
confidence: 92%
See 1 more Smart Citation